Komposisi Serat Makanan Beberapa Fraksi Sosoh Beras - E.Y. Purwani; D.S. Darmadjati; R. Sarini (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Brown rice of three varieties (IR-64, Cisadane and Pandan Wangi) were milled gradually to obtain milling fractions comprising 0-7.5% milling fraction I (FSI), 7.5-15% (FSII), 15-22.5%(FSIII), 22.5-30% (FSIV) and milled rice. The milling fraction and milled rice were analyzed for their dietary fiber components, protein, lipid and ash. The distribution of dietary fiber components in the milling fraction varied within rice varieties. Most of hemicellulose, cellulose and lignin were distributed in 0-7.5% ESL FSI contained 12-17% hemicellulose, 7-9% cellulose and approximately 3% lignin. FS H contained 1-8% hemicellulose, 3-4% celulose and 0.8-2% lignin, while the FS HI, FS IV and milled rice contained less than 1% hemicellulose, cellulose and lignin. Most of pectic substance (310%) was distributed in FS III and FS IV. Protein content of FSI, II 111 and IV varied from 11% to 18%. The highest lipid content (more than 18%) was observed in the FS I. The fractions from the outer portion contained higher amount of ash.